Synthesis, Isolation and Characterization of Process-Related Impurities in Oseltamivir Phosphate - Yogesh Kumar Sharma; Dau Dayal Agarwal; Sudesh Bhure; Sanjay Singh Rathore; Chakravir Rawat; Rajendranath Mukharjee (E-Journal of Chemistry)
Three known impurities in oseltamivir phosphate bulk drug at level 0.1% (ranging from 0.05-0.1%) were detected by gradient reverse phase high performance liquid chromatography. These impurities were preliminarily identified by the mass number of the impurities. Different experiments were conducted and finally the known impurities were synthesized and characterized.